Simultaneous Determination of Liver Blood Flow and Polygonal Cell Function in Hepatobiliary Diseases - Bláha, V.; Kolínská, J.; Blahníková, L.; Endrle, E.; Soušek, O.; Výška, K. (Nuklearmedizin - NuclearMedicine, 1969)
The present paper reports values for the extraction fraction of 131I-R.B. in the liver (E. F.) — as an index of the momentary ability of the polygonal cells to extract a foreign dye from the blood passing through the liver — in 457 patients with various types of liver damage and a group of controls.This value was obtained by means of the colloidal 198Au clearance and the 131I-Rose Bengal clearance determined simultaneously. In comparison with the control group the average value of the E. F. was decreased in the group of infectious hepatitis (~ 12%), and in the group of secondary or primary cancer of the liver (~ 14%o). An increase of the E. F. was observed in the group of fatty infiltration of the liver (~ 11%) and in the group of congestive heart failure (~13%).In the groups of chronic liver diseases with and without portal hypertension the average value of E. F. was almost the same as the value in the control group, but a great variation of individual values has been noticed. According to the authors’ opinion the value of E. F. in these groups as well as in the group of infectious hepatitis is closely related to the activity of the liver disease. This may be important for deciding the therapy, especially from the viewpoint of a possible indication to perform portocaval anastomosis.